LEARNING ACTIVITIES AND LEARNING OUTCOMES AFTER THE IMPLEMENTATION OF STUDENT TEAMS ACHIEVEMENT DIVISIONS OF COOPERATIVE LEARNING ON VIBRATION AND WAVE TOPICS - Roudhoutul Aulia Rochim; Nur Kuswanti; Noer Af’idah (Jurnal Pembelajaran Sains, 2021)
Evaluation of science learning achievement on conventional manner show that students were less active in the learning process, low cognitive performance, interest in learning science were low, and  difficulty in learning science topic. As a result student’s and learning achievement. The difficulty was caused by low teacher ability to manage it, so that the learning was less effective and interesting. Therefore, learning model is needed to support student mastery. One of them was cooperative learning model of student teams achievement divisions. This research aimed to describe the implementation of the syntax and student learning achievement after learning using cooperative learning model of student teams achievement divisions on Vibration and Wave. This study was a descriptive research with quantitative approach. It used One-Shot Case Study. The Subjects of this study were students of class VIII of State Junior High School 3 Jombang consisting of 30 students. The implementation of the syntax was observed by implementation of the syntax sheet. Learning achievement were determined based on mastery of learning achievement and mastery of learning indicator on minimal mastery criteria. The results of the research showed that: (1) Implementation of the syntax at the first and second meeting reached the average 89,5% with very good criteria , (2) Student learning outcome reached the average 77% while the learning indicator value got the average 86,5 with mastery category.